1991
DOI: 10.1210/mend-5-7-967
|View full text |Cite
|
Sign up to set email alerts
|

Transient Expression of Progesterone Receptor Messenger RNA in Ovarian Granuiosa Cells after the Preovulatory Luteinizing Hormone Surge

Abstract: The ovarian steroid progesterone affects reproductive physiology by regulating the expression of specific genes in target tissues. In an attempt to address the question of whether the ovary itself is a target tissue for progesterone action, we have examined the localization and regulation of progesterone receptor (PR) mRNA in the rat ovary. We used the polymerase chain reaction to clone the steroid-binding domain of the rat PR from uterine cDNA and used this as a probe to isolate a larger cDNA from a rat place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(176 citation statements)
references
References 58 publications
(90 reference statements)
14
159
0
2
Order By: Relevance
“…Our study solved this mystery by demonstrating an important role of ecdysteroids, the principal steroid hormones of Drosophila, in mature follicle cells for follicle rupture/ ovulation. Like preovulatory follicles that only transiently up-regulate progesterone receptor in granulosa cells before ovulation (46), mature follicles of Drosophila also adjust their expression of EcR receptors to allow EcR.B2 to remain functioning and promote ovulation. It is interesting that neither progesterone nor ecdysteroid signaling regulates mmp expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our study solved this mystery by demonstrating an important role of ecdysteroids, the principal steroid hormones of Drosophila, in mature follicle cells for follicle rupture/ ovulation. Like preovulatory follicles that only transiently up-regulate progesterone receptor in granulosa cells before ovulation (46), mature follicles of Drosophila also adjust their expression of EcR receptors to allow EcR.B2 to remain functioning and promote ovulation. It is interesting that neither progesterone nor ecdysteroid signaling regulates mmp expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from samples by using modified acid guanidinium-thiocyanatephenol-chloroform extraction procedures (Chomczynski & Sacchi 1987) ) and rat (M20133) ) androgen receptor, hu-man and rabbit (M12674, X03635, M11457) (Fuqua et al 1990;Greene et al 1986aGreene et al , 1986b and rat (Y00102) Koike et al 1987) estrogen receptor, human and rabbit (M15716) Misrahi et al 1987) and rat (S64044) (Park & Mayo 1991) progesterone receptor, and human and rabbit (M10277) (Nakajima-Iijima et al 1985) and rat b-actin (V01217, J00691) (Nudel et al 1983). The PCR conditions and number of cycles, which were selected after communication with Dr. Wilson (androgen receptor), computer analysis (Oligo 4.0 software, National Biosciences; and NCBI BLAST) and extensive experimentation, are shown in Table 2.…”
Section: Molecular Biological Proceduresmentioning
confidence: 99%
“…However, in granulosa cells, expression of the PR gene is not observed by stimulation with estrogen; the cAMP-protein kinase A (PKA) pathway has been documented to directly activate the distal promoter activity of the PR gene in the cells (Clemens et al 1998). Park and Mayo (1991) reported that PR mRNA was highly expressed in the granulosa cells of large follicles in the ovaries of animals treated with pregnant mare's serum gonadotropin (PMSG) followed by human chorionic gonadotropin (hCG). In in vitro culture of rat granulosa cells, high concentrations of either FSH or LH stimulated PR gene expression (Natraj & Richards 1993).…”
Section: Introductionmentioning
confidence: 99%